RESILIENSI PADA KARYAWAN YANG MENGALAMI PEMUTUSAN HUBUNGAN KERJA (PHK) - Apriawal, Jabbal (Universitas Ahmad Dahlan, 2013)
ABSTRACTEmployment problems faced by individuals today is more complex. One is the Termination of Employment (FLE) is something that is greatly feared by active employees in work that requires an ability to face and overcome, one of which is the resilience. The purpose of this study was to determine how the resilience of employees who experienced layoffs (layoffs). This study used a qualitative approach with case study method. The method of data collection used interviews and observations technique with a sampling of employees who have terminated employment with the age of 30-40 years.The results showed that individuals in the face of layoffs certainly different, there are individuals who are able to bounce back from the previous state but is less effective that even people who are able to get up and recover from negative situations effectively.Keywords: employee layoffs, the factors that affect resilience, the resilienceÂ